PENERAPAN TECHNOLOGY ACCEPTANCE MODEL UNTUK MENJELASKAN NIAT PEMBELIAN MELALUI APLIKASI GO-FOOD - Agung Dwi Nugroho; Muhammad Akbar; Ena Andini; Amir Hidayatulloh (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The purpose of this study is to analyze the application of techology acceptance model to explain purchase intentionthroug the Go-Food application. The population in this study is internet users. The sample in this research is theGo-Food application user. The sampling technique in this study uses purposive sampling, with the criteria for GoFood application users who have made at least two purchases through the Gofood application. Data collectionin research using a questionnaire with the help of Google Form. Respondents in this study were 157 respondents.Data analysis techniques in this study used Partial Least Square with the help of the WarpPLS tool. This studyfound that the intention to make purchases through the Go-Food application was influenced by word of mouth andperceived ease of use. However, the intention to make purchases using the Go-Food application is not affected bythe perception of usability. Other results show that the perception of ease of use affects the perception ofusefulness.